Blockchain and Green Sukuk Integration for Coastal Community Empowerment in Sustainable Blue Economy - Asrul Bastian Yunas; Rumanto, Yuliadi; Albart, Nicko (Research Horizon, 2025)
Digital transformation in the context of a sustainable blue economy opens up strategic opportunities to address various social, economic, and environmental challenges faced by coastal communities. This study examines the integration of blockchain technology and green sukuk financing instruments as an innovative strategy that has the potential to empower coastal communities inclusively. This research method uses a conceptual approach and literature study. The research findings show that collaboration between blockchain and green sukuk can improve efficiency, transparency, and accountability in the management of environmentally-oriented projects. In addition, this approach allows real-time tracking of funds, strengthens data-based reporting, and encourages active participation of local communities in conservation initiatives. This integration also plays an important role in expanding financial access for groups that have been marginalized, through an environmentally friendly sharia financing scheme. However, the implementation of this model is not without challenges, such as low digital literacy, limited technological infrastructure, and the absence of supporting regulations. Therefore, a gradual, collaborative implementation strategy is needed, and is adjusted to local conditions.